UTILIZING HOUSE YARDS TO GROW PRODUCTIVE CROPS AT PELAMBUAN SUB-DISTRICT, BANJARMASIN MUNICIPALITY - Andi Suci ANITA; Edward ZUBIR; Mukhyar AMANI (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2019)
Improving people’s welfare is the main goal of development, which can be achieved among others through the intensive use of house yards. Every community member owns a yard at their house. This activity is done in collaboration with housewives who are not working at Pelambuan Selatan sub-district, Banjarmasin, who have irregular monthly incomes. House yards are used effectively to cultivate vegetables and medicinal plants on organic media which are arranged vertically. Such use is expected to be able to help families meeting their daily nutritional needs or in case they need medicinal aids. This activity is also expected to be sustainable so that the yield can be sold for some extra household income. The methods applied in this program include (1) Dissemination on the Utilization of House Yards, Planting Techniques, and Information on Vegetable Crops and Medicinal Plants; (2) Provision of vegetables and medicinal plants seedlings and seeds, growing media, watering cans, and plant racks; (3) Mentoring to the partners on the process of seedling, planting, and maintenance.